"O culto à tradição de nossa gente": a fabricação do folclore sergipano em exposições museológicas (1948-1976) - Souza, Jean Costa (2019)
This work analyzes the strategies of fabrication and promotion of folklore based on the intellectual trajectory of José Augusto Garcez, Felte Bezerra and Bráulio do Nascimento and presents as a clipping the configuration of museum exhibitions from 1948 to 1976 in the state of Sergipe. It reconstructs aspects of the trajectory of the intellectuals in the field of production of folklore in Sergipe, the relational strategies mobilized by the agents regarding their positions in the field of production of national / regional folklore and the impacts promoted in the field of museums by creation of the Campaign of Defense of Brazilian Folklore and the Sergipe Folklore Subcommittee. The work explains how museums consist of commemorative surveillance strategies and constant retelling of narratives. Based on the theoretical and methodological reference of the sociologist Pierre Bourdieu, maps some agents and their networks of intellectual relations, having as a case study the creation of three folklore museums in Sergipe, summaries of the debates about folklore in the 1940s and 1970s in Brazil.